Characterization of horticultural farms in Cerro Punta, Chiriqui, Panama - Herrera, Rito (2021)
The objective of this study was to characterize horticultural farms in Cerro Punta, Highlands– Chiriqui; about socioeconomic and agri-environmental aspects, with emphasis on the pesticides used, Panama. About 31 farms were randomly selected and producers were surveyed. In addition, a random soil sampling was carried out in five locations, to proceed with the physical-chemical analysis and pesticide residues analysis, such as organophosphates, carbamates, pyrethroids and organochlorines. According to the results, 48% of those surveyed are between 41 and 55 years old, with education at the primary level in 39% of cases and 55% belong to farmers associations. The five main crops are potatoes, carrots, cabbage, lettuce and onion and 26% carry out animal husbandry. The production costs were variable, from less than USD 3500 to more than USD 14 000 per hectare per year; the yield ranged from 3.68 t. ha-1 to 52.62 t. ha-1; associated with the implemented technologies. About 77% of the producers use untreated chicken manure and 36 different pesticides are used in the area. The 52% of the farmers use complete personal protective equipment. Regarding the laboratory analysis, the soils have a loamy-sandy texture, with a pH between 5.7 and 6.5, organic matter content between 1.34% and 4.34% and the Effective Cation Exchange Capacity between 8.04 and 26.75.